Rising Sino-Japanese competition: perspectives from South-East Asian elites. Issue 1 (2nd January 2017) - Singh, Bhubhindar; Teo, Sarah; Ho, Benjamin
ABSTRACT: One of the biggest challenges for the East Asian region today is the Sino-Japanese relationship. Starting with the fishing trawler incident in September 2010, followed by Japan's nationalisation of the Senkaku/Diaoyu Islands, this relationship is experiencing an escalation of tensions in most, if not all, areas of the bilateral relationship. In response to the intensifying competition, China and Japan have elevated the importance of South-East Asia and the Association of Southeast Asian Nations (ASEAN) in their foreign policy strategies. Focusing on how elites from five South-East Asian states—Indonesia, Malaysia, the Philippines, Singapore and Vietnam—perceive the engagement of China and Japan with the region, this article poses two questions: (1) How do South-East Asian elites view the Sino-Japanese competition? and (2) How do South-East Asian elites view the role of ASEAN in managing the competition? The analysis here concludes that while some South-East Asian elites see opportunities in the Sino-Japanese competition, they nevertheless do not perceive it as an issue of critical significance. Instead, the concern lies generally with major-power dynamics, and particularly with Sino-US relations. ASEAN is viewed to lack the ability to manage the negative consequences of the Sino-Japanese competition, although its external balancing function has perceptibly helped to restrain any escalation of major-power tensions.